Chemical profile, biological activities, and molecular docking of Algerian Juniperus phoenicea berries - Bouchareb, Abderrezak; Djemel, Abdelhak; Kadi, Imededdine; Djemoui, Amar; Bensouici, Chawki; Atanassova, Maria; Zoukel, Abdelhalim; Benmohamed, Mokhtar; Ahmad, Sheikh F.; Attia, Sabry M.; Benaceur, Farouk; Zahnit, Wafa; et al. (Italian Journal of Food Science, 2024)
The chemical composition, antioxidant activities, and α-amylase enzyme inhibitory activity of Algerian Juniperus phoenicea L berries were quantitatively and qualitatively determined in this study. Essential oil (EO) and non-polar crude extracts from cyclohexane and ethyl acetate were prepared, and the chemical profile was determined using GC-MS technique. The predominant compound in the EO was α-pinene (76.03%), while communic acid (23.66% and 22.38%) was the main compound in both non-polar crude extracts. The antioxidant potential of the samples was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,20-azino-bis(3-ethylbenzothiazoline-6-sulfonicacid)-diammonium salt (ABTS), and phenanthroline. All samples showed weak antioxidant capacity. The antidiabetic effect was assessed in vitro using the α-amylase assay; a strong inhibitory effect against the α-amylase enzyme was detected for both cyclohexane and ethyl acetate extracts with IC50 (IC50 = 186.91 ± 5.74 mg/mL and IC50 = 351.48 ± 0.17 mg/mL, respectively). Finally, an in silico study was performed for both α-amylase and α-glucosidase proteins to enhance our outcomes.